Association Between Screen Time, Fast Foods, Sugar-Sweetened Beverages and Depressive Symptoms in Chinese Adolescents - Xu, Honglv; Guo, Jichang; Wan, Yuhui; Zhang, Shichen; Yang, Rong; Xu, Huiqiong; Ding, Peng; Tao, Fangbiao (Frontiers in Psychiatry, 2020)
Objective: Although previous studies have shown that screen time (ST), fast foods (FFs) and sugar-sweetened beverages (SSBs) consumption are associated with depressive symptoms in adolescents, research on these associations in Chinese adolescents is scarce. This study aimed to examine the association between ST, FFs, SSBs and depressive symptoms in Chinese adolescents, and explore the mediating effects of FFs and SSBs in the association between ST and depressive symptoms. Methods: This school-based nationwide survey was carried out among 14,500 students in four provinces of China. The Children's Depression Inventory was used to assess the participants’ depressive symptoms. ST, FFs and SSBs consumption were measured by a self-reported questionnaire. The Bayesian multiple mediation model was used to analyze the mediation effect. Results: ST, FFs and SSBs were more likely to be associated with depressive symptoms, and ORs (95%CI) were 1.075 (1.036 - 1.116), 1.062 (1.046 - 1.078) and 1.140 (1.115 - 1.166), after we adjusted for sociodemographic variables. Additionally, in Bayesian multiple mediation model, direct effect, mediating effect, total effect, ratio of mediating effect to total effect were 0.125, 0.034, 0.159,and 0.214, respectively. All path coefficients of the three mediation paths are statistically significant (p < 0.05). Conclusions: Our study demonstrates that ST, FFs and SSBs consumption are associated with depressive symptoms in Chinese adolescents. It is likely that FFs and SSBs partially mediate the association between ST and depressive symptoms by chain-mediating effects.